2014
DOI: 10.7314/apjcp.2014.15.21.9433
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Cervical Cancer Incidence and Mortality in the Pacific Region

Abstract: This study provides the first systematic literature review of cervical cancer incidence and mortality as well as human papillomavirus (HPV) genotype prevalence among women with cervical cancer in the Pacific Island countries and territories. The cervical cancer burden in the Pacific Region is substantial, with age standardized incidence rates ranging from 8.2 to 50.7 and age standardized mortality rate from 2.7 to 23.9 per 100,000 women per year. The HPV genotype distribution suggests that 70-80% of these canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…The cervical cancer disease burden in the Pacific Region is high, especially in the Melanesian countries where incidence ranks among the world’s highest (Ferlay et al, 2010; Garland et al, 2012; Obel et al, 2014). Current preventive efforts in the region do not match the burden of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cervical cancer disease burden in the Pacific Region is high, especially in the Melanesian countries where incidence ranks among the world’s highest (Ferlay et al, 2010; Garland et al, 2012; Obel et al, 2014). Current preventive efforts in the region do not match the burden of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of cervical cancer incidence and mortality found that the annual age standardized incidence and mortality rates for cervical cancer in the Pacific Region ranges between 8.2–50.7/100,000 and 2.7–23.9/100,000 respectively. This translates into approximately 800 new cases of cervical cancer and 500 preventable deaths per year (Parkin et al, 2008; Foliaki et al, 2011; IARC, 2012; Obel et al, 2014). The Melanesian island countries rank among the highest cervical cancer incidence and mortality rates in the world (Ferlay et al, 2010; Garland et al, 2012; IARC, 2012) and recent cancer registration from the Micronesian islands found similarly high cervical cancer incidence with the great majority of cases diagnosed at advanced stages (stage II or higher) which is beyond the on-island treatment capacity (Buenconsejo-Lum et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the Pacific region, cervical cancer rates are low for the general population in N.Z. However, Pacific peoples and the indigenous Maori experience a disproportionately higher rate of certain cancers and in particular, infectious related cancers such as cancer of the cervix (Foliaki et al, 2011;Obel et al, 2014) and liver (Foliaki et al, 2004;Meredith et al, 2012). Pacific women also have higher rates of other gynaecological cancers (endometrial, ovarian) (Meredith et al, 2012).…”
Section: Barriers To Cervical Screening Among Pacific Women In a Newmentioning
confidence: 99%
“…Cervical cancer accounts for 11% of female cancer death in developing countries and is a leading cause of cancer death among women in the Asia-Pacific region (Jemal et al, 2011;Obel et al, 2014). Histologically, squamous cell carcinoma is the most common type of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%